I can help - Costello, David (New York : Farrar Straus Giroux, 2010)
When a duck gets lost and a monkey helps him find his way, it starts a chain reaction in which all the young animals help each other solve their problems.
Keywords: Cooperation -- Juvenile fiction; Animals -- Juvenile fiction